Komitmen Afektif: Peran Kepemimpinan Melayani, Keterlibatan Kerja, dan Lingkungan Kerja - Azahari Ramadan Azis; Ignatius Soni Kurniawan; Mohammad Ahyar Syafwan Lysander (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study examines the influence of melayani leadership, work engagement, and the work environment on employees’ affective commitment. The research aims to identify factors that strengthen employees’ emotional attachment, especially where interpersonal relationships and job characteristics are important. The study identifies variables that significantly contribute to affective commitment and evaluates the predictive value of the work environment. A quantitative survey approach was used and analyzed through hypothesis testing. The results show that melayani leadership and work engagement significantly increase affective commitment, indicating that supportive leadership and high involvement strengthen employees’ emotional bonds. However, the work environment shows no significant effect on affective commitment. These findings show that relational and psychological factors are stronger determinants of emotional attachment than environmental conditions. Overall, the study supports existing theories on leadership and engagement and provides practical guidance for strengthening affective commitment.